Experiences and challenges of adults living with type 2 diabetes mellitus presenting at the University Teaching Hospital in Lusaka, Zambia. Issue 1 (15th November 2019) - Mwila, Kunda Faith; Bwembya, Phoebe Albina; Jacobs, Choolwe
Abstract : Objective: The study explored the experiences and challenges of adults living with type 2 diabetes mellitus (T2DM) presenting at the University Teaching Hospital (UTH) in Lusaka. Research design: A qualitative descriptive study was conducted. The research relied on purposive sampling to select 28 participants for in-depth interviews. Participants were interviewed during clinical visits at UTH. Results: Views from participants showed that some adults living with T2DM experienced physical and mental illnesses. Participants' views reflected that their livelihood with T2DM was influenced by family support, poor or non-adherence to treatment guidelines and access to information, education and communication materials. The most important challenges reported were psychosocial and financial. Conclusion: The study concluded that some adults living with T2DM experience a lot of physical sicknesses and their challenges, especially of the psychosocial nature may require professional attention. However, particular attention should be paid to the patient's self-care and psychosocial therapy. Self-care protocols should be tailored to complement the different types of patients with diabetes and improve their quality of life.Cite Now